Development Strategy the Balance of Environment against Green Factory of the Infectious Garbage Displacement Nakhon Sawan Province - Somboonkittikorn, Pinyapat; Lerkrai, Direk; Wongkamjan, Supawan (Richtmann Publishing, 2013)
The objectives were 1) to create strategy for developing the balance of environment against green factory of the infectiousgarbage displacement, Nakhon Sawan Province and 2) to experiment strategies for developing the balance of environmentagainst green factory of the infectious garbage displacement, Nakhon Sawan Province. Qualitative research and quantitativeresearch approaches were used. Data collection and analysis were done with In-Depth interview for qualitative research. Theexperiment group was 50 community peoples from the twelfth Village, Moo Ban Nhong Khaeng and the control group was 25community peoples from the first Village, Moo Ban Thup Chumpol in Nakhon Sawan Province. The experimental and controlgroups were selected with Purposive Sampling Technique. The results of the development strategy by replacing the frameworkfor the strategic development of the theory of Corporate Social Responsibility (CSR) that consists of three units: 1) analysis ofthe problem and the need to assess the problems and needs between plant and communities and 2) to evaluate the ability ofthe plant and meet the needs of the community, and 3) to evaluate the satisfaction of the neighboring communities. Theexperimental results of the 50 community peoples showed that their satisfaction evaluation had posttest mean score with 4.83,was higher than control group mean score with 4.61 at statistically significant at level 0.5. Moreover their satisfactionevaluation had posttest mean score with 4.83, was higher than pretest mean score with 3.44 at statistically significant at level0.001.